Estrategia de exportación desde Argentina hacia México de cuadernos de espiral - Páez, Héctor Ricardo (2008)
In this pa per we analy ze the fea si bi lity of ex por ting spi ral no te books from Argen - ti na to Me xi co. We con si der this pos si bi lity for a lea der Argen ti nean en ter pri se both, the Argen ti nean and Me xi can mar kets are stu died, and al so the stra te gic po -si tio ning of the se ve ral en ter pri ses ope ra ting in the Me xi can mar ket. We al soin clu de a sen si ti ve analy sis on the ex chan ge ra te, gi ving as a re sult se ve ral al ter na ti ve sce na rios